INNOVATION PERFORMANCE IN COMPLEX SYSTEMS SUPPORTED BY EVOLUTION AND INTEGRATION BETWEEN THE QUALITY AND KNOWLEDGE MANAGEMENT - Martins, Francisco José (Revista Interface Tecnológica, 2020)
The consolidation and certification of quality management systems, with the expected benefits, presents many studies on the theme, however, a smaller number of works relating them to the necessary integration with knowledge management and the analysis of the external operating environment of the business, seen as a complex and highly dynamic system, as well as the necessary changes based on new technologies and the effective contribution of these systems in innovation performance for organizations. In this context, the objective of this work was to rescue concepts about the evolution of quality management systems and their integration with knowledge management and the expected performance in innovation, justified by the relevance of the theme in the current and future scenarios, which presents a greater challenge for the managers in the organizations, as well as their scope in increasingly dynamic environments. It is concluded that the continuous improvement and integration of the management processes, duly supported by the leaders, should also foster innovative performance, and should be the focus of attention of the managers involved, especially in the developing small and medium-sized companies, as a factor of survival and growth.